Análise de crescimento do amarilis cultivado a pleno sol - Mateus, Caroline de Moura D'Andréa [UNESP]; Pivetta, Kathia Fernandes Lopes [UNESP]; Bôas, Roberto Lyra Villas [UNESP]; Coan, Ruchele Machiori [UNESP] (FapUNIFESP (SciELO), 2010)
Cultivation of amaryllis (Hippeastrum X hybridum Hort.) is mainly intended for production and commercialization of bulbs for export. Information on amaryllis growth cycle is still inconsistent, therefore this study was carried out to gather data that will contribute to studies on growth analysis of amaryllis var. Orange Souvereign in full sun. The experiment was arranged in a complete randomized design, with 4 repetitions and 10 plants per repetition for each analyzed characteristic. Plants were grown in an area of 2 ha and data were collected monthly over a 14 month period. The leaf area determined at the end of the experiment was on average 3102.65 cm2 , considering 10 leaves per plant. Bulb diameter increased gradually throughout the period of production, ending, at 420 days after planting, with 9.15 cm on average. Total fresh mass at the end of the cycle was on average 1050.55 g, of which 39 % consisted of bulb fresh mass, which is the traded form (bulb +roots). The physiological indices of the growth analysis showed the plant behavior in the field, under the conditions found in Santo Antonio de Posse, São Paulo State, Brazil, with the assimilatory system having achieved a good performance in these growing conditions. Growth of amaryllis is considered satisfactory in this region, from the point of view of trading , as it can reach the standards required for export.

O cultivo de amarílis (Hippeastrum x hybridum Hort.) visa, principalmente, à produção e comercialização de bulbos para exportação. Informações sobre o seu ciclo de crescimento ainda são incongruentes. Assim, foi objetivo realizar medições que possam contribuir com estudos de análise de crescimento do amarílis var. Orange Souvereign, cultivado a pleno sol, nas condições encontradas em Santo Antônio de Posse, Estado de São Paulo. O delineamento experimental empregado foi o inteiramente casualizado. Utilizaram-se plantas cultivadas em uma área de 2 ha, onde os dados foram coletados mensalmente, durante 14 meses, de forma aleatória. Para cada uma das características analisadas foram utilizadas quatro repetições de 10 plantas. A área foliar determinada ao final do experimento foi de, em média, 3.102,65 cm2 , tendo em vista 10 folhas por planta. O diâmetro do bulbo aumentou, gradualmente, durante todo o período de produção, finalizando aos 420 dias após plantio, com 9,15 cm em média. A massa fresca total ao final do ciclo foi de, em média, 1.050,55 g, dos quais 39% (410 g) foram de massa fresca obtida pelo bulbo da forma como é comercializado (bulbo + raízes). Os índices fisiológicos da análise de crescimento (taxa de crescimento absoluto, taxa de crescimento relativo, taxa de assimilação líquida e razão de área foliar) demonstraram o comportamento da planta no campo, tendo o sistema assimilatório atingido bom desempenho nas condições de cultivo. O crescimento de amarílis foi considerado satisfatório do ponto de vista comercial.
Growth analysis of amaryllis (Hippeastrum x hybridum Hort.) grown in full sun
Keywords: Floriculture; Hippeastrum X hybridum Hort.; Physiological indices; Ornamental plants; Hippeastrum x hybridum Hort.; Floricultura; Plantas ornamentais; Índices fisiológicos